PENINGKATAN KEMAMPUAN MENULIS DENGAN MENERAPKAN MODEL ARTIFICIAL INTELLIGENCE (AI) BERBASIS NATURAL LANGUAGE PROCESSING (NLP) DENGAN INDOBERT - Lina Siti Nurwahidah; Indriyani, Iin; Rivan Syahrul Falah; Popon Rohaeti; Yuli Yulianti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
Abstract Essay writing skills are an important aspect of education because they help improve students' critical and analytical thinking abilities. This study discusses the results of applying an Artificial Intelligence (AI) model based on Natural Language Processing (NLP) to enhance students' essay writing skills in Senior High Schools (SMA). The specific objectives are: (1) to implement an IndoBERT-based NLP model that can identify grammatical errors and provide suggestions for improvement in students' essays; (2) to test the effectiveness of this model through experiments in high schools by comparing groups that use the AI application with a control group that does not; and (3) to obtain responses from students and teachers regarding the use of NLP-based AI in improving writing skills, including sentence structure, grammar, and depth of argumentation.This research was conducted with twelfth-grade students at SMAN 1 Garut in the 2025–2026 academic year. A mixed-methods approach with a Sequential Explanatory design was used, beginning with a quantitative phase to test the effectiveness of the model, followed by a qualitative phase to gain an in-depth understanding of the dynamics of IndoBERT use in essay writing classes.The findings indicate that the application of this model is effective for essay writing. This is evidenced by a p-value of 0.002 (< 0.05). The mean difference of 10.281 demonstrates a substantial improvement in the experimental class. Furthermore, qualitative data from interviews with teachers and students showed positive responses. Keywords: essay writing, IndoBERT, mixed method